"I just believe there is a risk" understanding of undetectable equals untransmissible (U = U) among health providers and HIV‐negative partners in serodiscordant relationships in Kenya. Issue 3 (6th March 2020) - Ngure, Kenneth; Ongolly, Fernandos; Dolla, Annabell; Awour, Merceline; Mugwanya, Kenneth K; Irungu, Elizabeth; Mugo, Nelly; Bukusi, Elizabeth A; Morton, Jennifer; Odoyo, Josephine; Wamoni, Elizabeth; Barnabee, Gena; et al.
Abstract: Introduction: Sustained HIV viral suppression resulting from antiretroviral therapy (ART) eliminates the risk of HIV transmission, a concept popularly framed as Undetectable = Untransmittable (U = U). We explored knowledge and acceptance of information around the elimination of HIV transmission risk with ART (U = U) in Kenya. Methods: Our qualitative study was conducted within a project evaluating the use of pre‐exposure prophylaxis (PrEP) integrated into ART care for HIV serodiscordant couples in public clinics in Kenya (the Partners Scale Up Project). From February 2017 to April 2019, we conducted semi‐structured key informant interviews with 83 health providers and in‐depth interviews with 61 HIV‐negative people in serodiscordant relationships receiving PrEP services. Transcripts were coded using thematic analysis. Results: Health providers reported being aware of reduced risk of HIV transmission as a result of consistent ART use and used words such as "very low, " "minimal" and "like zero" to describe HIV transmission risk after viral suppression. Providers reported finding viral load results helpful when counselling clients about the risk of HIV transmission. Many lacked confidence in U = U and counselled on consistent condom use even after viral suppression while some expressed concerns that communicating this message to people living with HIV (PLHIV) would lead them to engage in multiple sexual relationships. Other providers reported that they did not counsel about the reduced risk of HIV transmission after viral suppression for fear of being blamed if HIV transmission occurred. HIV‐negative partners reported being informed about U = U by providers but they did not believe nor trust the message. Even after their partners achieved viral suppression, some HIV‐negative partners were unwilling to stop PrEP, while others indicated that they would use condoms if they stopped PrEP to be sure that they were protected from HIV. Conclusions: Despite awareness that effective ART use eliminates HIV transmission risk, there is both a lack of in‐depth knowledge and conviction about the strategy among health providers and HIV‐negative partners in serodiscordant relationships. New strategies that go beyond communicating the science of U = U to consider the local social and clinical environments could maximize the effectiveness of U = U.